Unmet needs of care and associated factors among stroke survivors followed up at the Neurology Clinics, National Hospital of Sri Lanka - J. Hamsananthy; V. Kumarapeli; S. Jeevatharan; R. Gamage (College of Community Physicians of Sri Lanka, 2015)
Journal of the College of Community Physicians of Sri Lanka 2014; 20(1): 49-56